Comparative Analysis of The Impact of Number and Level of Participation in Extracurricular Activities on The Academic Achievement of Students with Special Needs - Bastiana, Bastiana; St, Kasmawati; Meidina, Tatiana (Specijalna edukacija i rehabilitacija, 2025)
Introduction. This research aims to examine the effect of participation and involvement of students with special needs in extracurricular activities on their academic performance in high schools in Makassar. Objectives. The primary objective of this study is to investigate the positive and significant impacts of the number of extracurricular activities and the level of participation in these activities on the academic performance of students with special needs. Methods. This study employs simple and multiple linear regression methods on a sample of 72 students with special needs who are active in extracurricular activities. Results. The results indicate a positive and significant effect of both the number of extracurricular activities participated in and the level of participation in these activities on students’ academic performance. Conclusion. This research concludes that participation and involvement levels in extracurricular activities are important factors that can enhance the academic performance of students with special needs. Based on these findings, it is recommended that schools increase opportunities for participation and facilitate higher levels of involvement in extracurricular activities for students with special needs to maximize their potential for skill development and academic achievement.
Keywords: involvement; participation; extracurricular; academic achievement